PERAN FOOD AND AGRICULTURE ORGANIZATION (FAO) DALAM MEMBANTU KRISIS PANGAN DI AFGHANISTAN (2007-2011) - Ruli Prastio; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research explain about role of international organization FAO on getting into a scrape food crisis disaster. This research using a descriptive explanative to explain about food crisis in Afghanistan. According Maflecroft report Afghanistan as become the first country getting into trouble food insecurity. It is certainty impact to food sovereignity so it will effecting on food crisis. Afghanistan’s food crisis is caused two things. First, situation NATO army Attack’s to invation Taliban terorist movement. Taliban have been hiding Al Qaeda terrorist who have blow up World Trade Center Building in United State of America. NATO’s coming to Afghanistan is not just to war on terror, but they have an a agenda to fight opium production and war mass destruction. Second, global climate change on 2007 have been effecting to flood and dryness. It caused Afghanistan have ekstrim climte change, mountain range and bad irrigation. The two tragedies exactly impact to Afghanistan agriculture land production. It will caused land broken and fail of harvest. The role of FAO is a institusional as specially ward off food problem and agriculture with gave first help as known technical cooperative program (TCP) and continue program.This research using role of international organization theory by Clive Archer and non-traditional threat theory by Barry Buzan. The role of international organization theory by Archer have can be explain that is have three functions, that is International organization can be as a instrument. independent actor and the arena for development and develop countries. And then Barry Buzan with non-traditional threat theory known there is any three things kind of threat have been to fight a world. They are : economic threaten. social threatean. environment threaten. This theory as relevan with Afghanistan had been around whose cannot handle food crisis problem. Espcially theory by Buzan about environment threaten whose said that environment threaten is threaten which is caused global climate change, pollution and becoming thin ozone layer it will impact to flood and dryness. This problem have been impact to economy and politics Afghanistan in internasional world. Moreover, Afghanistan’s problem have been make this country as known a failed country.The result show that FAO just can help Afghanistan as big as 70 %. It through out indicator a program in Afghanistan. It is caused some household success percentage self-suffiance rate 50-70%. It seen from Emergency Irrigation Rehabilitation Project (EIRP) 40% and social-economic programme 30 %. Moreover, Afghanistan needs import principle commodity with neighbour countries like Pakistan, Kazakhtan and Uzbekistan. Principle commodity in Afghanistan coming out at 6 million MT and just 4 Million MT can be suffienciently.Keywords: food crisis, terrorism, global change, technical cooperative program (TCP), International Organization.